PENGEMBANGAN MEDIA PLEACE O’CLOCK PADA POKOK BAHASAN PECAHAN UNTUK SISWA SDN 4 JENGGIK - Ramdan, Ahmad Yasar; Atiaturrahmaniah, Atiaturrahmaniah (Profesi Pendidikan Dasar, 2019)
This research aimed to find out the validity and effectiveness of pleace o’clock media as the developed products and to find out students’ achievement test. The development procedures used Borg and Gall model which had been modified into 8 stages. The subjects of this study were 23 of fifth grade (V) students of SDN 4 Jenggik. Data collection techniques used in this study were validation sheets, achievement test, and students’ response questionnaire. The results from expert validators, or from media experts obtained 55 scores, then the average scores were 4.23 which were indicated as "excellent". Meanwhile, material experts obtained 37 scores, then the  average scores were 3.36 and indicated as "sufficient". The results of students’ response questionnaire obtained 268 scores or reached 89.76%. Hence,  based on the conversion table, the score was indicated as "good" category. Meanwhile, the learning achievement test with the total number  of 23 students,  where 21 students had completed, with the percentage of completeness was 91, 30%. Thus, it can be concluded that the use of the o’clock pleace media on fractions was effective in the learning process in fifth (V) grade students of SDN 4 Jenggik.